Analysis of Chemistry textbooks: a view on the didactic unit atomic models - Leice Milla Ribeiro de Novais Novais; Everton Bedin (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2023)
This research aims to present an analysis in five Chemistry Textbook (CT) about the presence of elements that can contribute to the scientific and critical formation of students in the light of the didactic unit Atomic Models. To this end, documentary research was carried out, with a qualitative approach, based on the guiding principles: Contextualization, Interdisciplinary, Scientific and Technological Literacy, Science-Technology-Society and Review Questions. Given the results obtained, it was found that, in the didactic unit investigated, the analysed axes do not have expressiveness in the different CTs, as they appear mostly superficially and with few possibilities of use and exploration by the teacher in the classroom. However, it should be noted that this analysis took place in an interpretative-intuitive way, considering the assumptions of each axis, in addition to being restricted to a single didactic unit of the CT, not allowing, therefore, to reach comprehensive conclusions about each collection, when considered in its entirety.